2012
DOI: 10.1021/mz300210w
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Click Modification of Conducting Polymer Surface Using Cu(I) Species Generated on a Bipolar Electrode in a Gradient Manner

Abstract: The electro-click reaction of azide-functionalized poly(3,4-ethylenedioxythiophene) (PEDOT-N 3 ) and a terminal alkyne was investigated using electrogenerated Cu(I) species on a bipolar electrode in a gradient manner. The introduction of a perfluoroalkyl group derived from the alkyne moiety onto the PEDOT surface only at the cathodic part of the bipolar electrode was successfully characterized by X-ray analyses and the surface properties of the modified film were studied. The spectroscopic analysis of the rhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
(33 reference statements)
0
47
0
3
Order By: Relevance
“…The fluorine-content profile revealed that the electrogenerated Cu(I)-mediated click reaction reflected the potential profile on the BPE (Figure 5b). 27 Then, the surface property of the gradually perfluoroalkylated PEDOT was investigated by measuring the static contact angle of a water droplet on the film. As expected, the contact angle at the fluorinated surface was significantly larger than that at the pristine surface (Figure 5c).…”
Section: Electro-click Modification Of Conducting Polymer Surfacementioning
confidence: 99%
“…The fluorine-content profile revealed that the electrogenerated Cu(I)-mediated click reaction reflected the potential profile on the BPE (Figure 5b). 27 Then, the surface property of the gradually perfluoroalkylated PEDOT was investigated by measuring the static contact angle of a water droplet on the film. As expected, the contact angle at the fluorinated surface was significantly larger than that at the pristine surface (Figure 5c).…”
Section: Electro-click Modification Of Conducting Polymer Surfacementioning
confidence: 99%
“…Its application to electroclick was reported recently by Shida et al [382]. A PEDOT-N 3 coated bipolar electrode could be functionalized only on its cathodic part and in a gradient manner with various alkyne-bearing molecules (Fig.…”
Section: Figure 16mentioning
confidence: 95%
“…Cu(I) ions are indeed unstable in the presence of dissolved oxygen, which restricts their diffusion and permits the coupling reactions to occur only close to the electrode. Consequently, micro-electrodes [330], local probe microscopies [380,381], bipolar electrodes [382] and gradient devices [383,384] have been used to locally induce electroclick as described in Fig. 17.…”
Section: Functionalization Patterning By Using Electroclickmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of stenciled 135 or bipolar 136 "e-click", surface gradients of covalently bound alkyne-bearing molecules were created on azide-functionalized conductive polymers.…”
Section: Electrochemically Driven Surface Chemical Reactionsmentioning
confidence: 99%